(untitled) (Revista de Medicina Clinica, 2021)
Introduction. Closed traumatic injuries and vascular accesses are the most common causation of pseudoaneurysms in peripheral arteries. Case report. A 71-year-old male who reports two weeks of evolution with increased volume and pain in the hypothenar region of the right hand, after hollow needle puncture. History of drug addiction. Physical examination shows edema, erythema, increased volume, pulsatile, ecchymosis, and pain at the mobilization of the 4th and 5th finger, preserved capillary filling, without peripheral nerve involvement. Angiotomography: ulnar artery with marked dilation in its distal third suggestive of a pseudoaneurysm. Transoperative broken pseudoaneurysm is confirmed, performing a resection of Pseudoaneurysm with contained clot. Discussion. Improvement of pain, decrease in volume, correct distal capillary filling, no paraesthesia, and functional. Pseudoaneurysms of the distal ulnar artery by puncture are uncommon. Surgical resection in peripheral areas is a feasible alternative. Keywords: Pseudoaneurysm, hypothenar, ulnar artery, puncture, treatment.